DESKRIPSI KADAR TIMBAL DALAM DARAH DAN JUMLAH ERITROSIT PADA PEKERJA BATIK - Purwati -; Indah Tri Susilowati; Dewi Saroh; Kartika Pertiwi (LPPM Universitas Abdurrab, 2025)
In the batik industry that uses synthetic dyes as batik dyes, batik industry workers are at risk of exposure to lead contained in synthetic dyes. Continuous exposure to lead can cause health problems and damage erythrocytes, thereby shortening the life of erythrocytes and reducing the number of erythrocytes. This study aims to determine the levels of lead in the blood and the number of erythrocytes in batik industry workers in Banaran Village, Grogol, Sukoharjo. The method used in this study is a descriptive cross-sectional method and a purposive sampling method, as many as 25 respondents who meet the criteria and have filled out the informed consent. The examination data were analyzed using a bivariate test with a significance level used to test the significance of the relationship is <0.05. The results obtained showed that the levels of lead in the blood of 25 respondents were still within the normal threshold according to the CDC, which is <10 µg / dL with lead levels between 0.03 µg / dL-4.896 µg / dL. The results of the erythrocyte count examination showed that 1 (4%) respondents had a lower than normal erythrocyte count and 24 (96%) respondents had a normal erythrocyte count. Lead levels in batik industry workers in Banaran Village, Grogol, Sukoharjo are still within the normal threshold according to the CDC and most batik industry workers have normal erythrocyte counts.